Public Oncologic Serum Biobank. (7th October 2014) - Rondot Radío, Pedro; Puricelli, Lydia
The Public Oncologic Serum Biobank is a not for-profit organization that has been established within the academia setting since 2009, which aims to prospectively collect and store serum samples from cancer patients and volunteers and their associated clinical and epidemiological data, with the ultimate goal to distribute them to the local and international research community focusing in understanding and improving cancer diagnosis and treatment.